Chlamydia trachomatis’ struggle to keep its host alive - Sixt, Barbara S. (Microb Cell, 2017)
Bacteria of the phylum Chlamydiae infect a diverse range of eukaryotic host species, including vertebrate animals, invertebrates, and even protozoa. Characteristics shared by all Chlamydiae include their obligate intracellular lifestyle and a biphasic developmental cycle. The infectious form, the elementary body (EB), invades a host cell and differentiates into the replicative form, the reticulate body (RB), which proliferates within a membrane-bound compartment, the inclusion. After several rounds of division, RBs retro-differentiate into EBs that are then released to infect neighboring cells. The consequence of this obligatory transition between replicative and infectious forms inside cells is that Chlamydiae absolutely depend on the viability and functionality of their host cell throughout the entire infection cycle. We recently conducted a forward genetic screen in Chlamydia trachomatis, a common sexually transmitted human pathogen, and identified a mutant that caused premature death in the majority of infected host cells. We employed emerging genetic tools in Chlamydia to link this cytotoxicity to the loss of the protein CpoS (Chlamydia promoter of survival) that normally localizes to the membrane of the pathogen-containing vacuole. CpoS-deficient bacteria also induced an exaggerated type-1 interferon response in infected cells, produced reduced numbers of infectious EBs in cell culture, and were cleared faster from the mouse genital tract in a transcervical infection model in vivo. The analysis of this CpoS-deficient mutant yielded unique insights into the nature of cell-autonomous defense responses against Chlamydia and highlighted the importance of Chlamydia-mediated control of host cell fate for the success of the pathogen.